PERMINTAAN PANGAN RUMAHTANGGA PROVINSI RIAU: MODEL LINEAR APPROXIMATE ALMOST IDEAL DEMAND SYSTEM - Heriyanto Heriyanto (Jurnal Agribisnis, 2018)
This study aimed to analyze the food consumption pattern of households by income level and education, to analyze the factors affecting the dominant staple food consumption expenditure of households, and to analyze the response of trees to food expenditure dominant factors that influence it. For research purposes constructed model Almost Ideal Demand System (AIDS), with Seemingly Unrelated Regression (SUR) method. The food commodities included in the model comprised of seven primary commodities. rice and sago, milk, beef and chicken, salt, sugar, cooking oil, as well as vegetables and fruits. The results showed that at a higher level of income, the proportion of food expenditure to others tends to decrease. The higher the housewives education’s level, the higher the consumption of dairy, beef and chicken, vegetables and fruits, while the consumption of rice and sago, sugar, and cooking oil tends to decline. Most of the parameter estimates of commodity prices and household income level of dominant influence consumption for each commodity group. Price's elasticity of all commodities tend to be negative and not responsive to the price changes. Similarly, cross elasticities showed the consumption expenditure of each commodity is not responsive to changes in other commodity prices. However, according to its income elasticity, four commodities (beef and chicken, as well as vegetables and fruits), are responsive to changes in income. From these findings, it can be stated that the policies related to the efforts to increase revenues performed better than price control policy. The efforts to improve household income is important to increase the consumption, particularly consumption of beef and chicken, as well as vegetables and fruits